Removal of Phosphorus and Recovery in Advanced HA-A/A-MCO Sludge Reduction Process - Zuo, Ning; Ji, Fang-Ying (Asian Journal of Chemistry, 2013)
In order to explore the method of improving phosphorous and nitrogen removal in sludge reduction technologies, an advanced process combining excess sludge reduction and phosphorous and nitrogen removal is developed, for short, HA-A/A-MCO process. The researching results show that when the amount of sidestream phosphorous removal sewage is 13 % of influent flow and the effluent phosphorous content of chemical phosphorous removal tank is 5 mg/L, effluent total phosphorus is less than 0.5 mg/L, which can fully meet the demand of First-degree-A Standards of GB18918-2002. Besides, increasing the phosphorous content from anaerobic release and controlling the effluent phosphorous content of chemical phosphorous removal tank being 5 mg/L can improve efficiency of chemicals, reduce medicament consumption and increase the phosphorous content of chemical sludge. And the phosphorous content of chemical sludge in HA-A/A-MCO system can be up to 18 %, which is equivalent with the content of phosphorous and can be recycled as production raw material of phosphorus fertilizer, replacing phosphate rock.